Pilot Plant Study to Utilize Waste Brine Generated by Salt Industries - Farhan Ullah Khan; Majid Mumtaz; Tehseen Ahmed (Journal of Basic & Applied Sciences, 2021)
Since early 80s, people of Pakistan have been enjoying good quality of salt known as refined salt. Mechanical salt washing is used in many countries to upgrade salt quality. The counter current washing at multiple stages and dewatering by centrifuge improves salt quality. During this process almost 10 to 15% of salt is converted into saturated brine solution containing high amount of sodium chloride, calcium, magnesium, potassium and sulphate. In the current practice most of the salt processers, this brine waste solution is drained. In the present study, a method is modified to utilize this waste brine solution. Brine was treated with calcium oxide and iron chloride to remove some soluble and insoluble impurities. The treated brine is evaporated in a specially constructed jacketed crystallizer connected with a hot water geyser. Heat is transferred through bottom by counter current flow. The temperature is maintained between 55 to 65oC at pH 3-4. The applied study yield the well shaped pyramidal crystals of salt known as Fluer de sel (flower of salt), that are world famous and used in gourmet foods with a growing market. Fleur de Sel has unique morphology, lower bulk density, large surface area, improved taste and rapid dissolution as compared to the common cubic salt